Angioplasty for pediatric renovascular hypertension: a 13-year experience - Zhu, Guangchang (Diagn Interv Radiol, 2014)
PURPOSE: We aimed to evaluate the long-term outcome and efficacy of percutaneous transluminal renal angioplasty (PTRA) for pediatric renal artery stenosis (RAS), which is an important cause of medication-refractory pediatric hypertension. MATERIALS AND METHODS: We retrospectively evaluated 22 hypertensive children (age range, 3–17 years) who underwent PTRA from February 2000 to July 2012. Sixteen patients had Takayasu arteritis and six fibromuscular dysplasia. Five were not included in the statistical analysis due to loss to follow-up. RESULTS: Technical success was achieved in 32 of 34 procedures (94.1%). The stenosis rate decreased from 84.5% before PTRA to 20.1% after PTRA. Treatment was effective in 72.7% (16/22) of patients, including complete cure in 27.3% (6/22) and improvement in 45.5% (10/22). Systolic and diastolic blood pressures decreased from 153±19.1 to 131.7±21.4 mmHg and from 97.9±14.2 to 83.6±19.3 mmHg, respectively (P < 0.01). Number of antihypertensive agents decreased from 2.7 to 0.5 per patient. Restenosis was detected in 40.9% (9/22) of patients, with a restenotic interval of 11.8 months (range, 3–47 months). Lesion length was strongly correlated with clinical success (cure and improvement) (independent-sample t test, P < 0.001; binary logistic regression, P = 0.040). CONCLUSION: Lesion length is an important determination of clinical success with PTRA for pediatric RAS. PTRA is an appropriate treatment option for pediatric renovascular hypertension due to Takayasu arteritis and fibromuscular dysplasia.